REVIEW OF ORGANIC AND INORGANIC WASTE MANAGEMENT AND STUDENT AWARENESS IN AL-AZHAR HIGH SCHOOL ENVIRONMENT MEDAN - Nathan Althaafarizq; Aufaa Azizi; Fauzan Arkan; Muhammad Radhin Pasha; Ahmad Fadhlan Syam Nasution (PT. Radja Intercontinental Publishing, 2025)
Effective waste management in the school environment is a strategic step in shaping environmental care behaviour from an early age. This study aims to review the practices of organic and inorganic waste management in schools and assess the level of students' awareness of the importance of sustainable waste management. The method used is a qualitative descriptive study with observation techniques, interviews, and the distribution of questionnaires to school staff. However, the implementation is not consistent and is still limited to administrative aspects related to waste management, but the implementation in the field is still not optimal. The level of students' awareness of the importance of waste management is in the medium category, with the main motivation coming from the influence of teachers and school environment programs. This study suggests the need to improve environmental education in a sustainable manner and provide adequate waste management facilities as a form of support for environmentally friendly behaviour among students.